Modelling the economic impact of substandard uterotonics on postpartum haemorrhage in Nigeria: safeguarding medicine quality can reduce costs and contribute towards universal health coverage - Ahmet Metin Gülmezoglu; Sachiko Ozawa; Sara Rushwan; Yi-Fang Ashley Lee; Colleen R Higgins; Petra Procter; Chimezie Anyakora; Lester Chinery (BMJ Public Health)
Introduction Little evidence exists on the economic threat that substandard uterotonics pose to postpartum haemorrhage (PPH), maternal mortality, and national health systems. For clinical emergencies such as PPH, the quality of the uterotonic drugs required for prevention and treatment plays a central role in whether a severe outcome or fatality occurs and has a direct knock-on effect on the cost of further treatment and care. We modelled the health and economic burden of substandard uterotonics on PPH in Nigeria.Methods A decision-tree model was built to simulate women giving birth in various healthcare settings, using uterotonics of varying quality, and facing PPH risks. We used the Demographic and Health Survey for care-seeking data and the Cochrane review for uterotonic effectiveness. Trial data from the Early detection of postpartum haemorrhage and treatment using the WHO MOTIVE bundle (E-MOTIVE) was applied for health outcomes by oxytocin quality. Scenarios were compared with and without substandard uterotonics.Results We estimated that using substandard uterotonics led to avertable out-of-pocket and productivity losses totaling US$89 million (~₦ 68.4 billion) annually in Nigeria. These avertable losses were the result of using substandard uterotonics in 1.6 million mothers. Without substandard uterotonics, healthcare providers can avert nearly 75 000 preventable PPH cases, reduce uterotonic use, save blood transfusions and avert around 1500 maternal deaths due to PPH annually in Nigeria.Conclusion This study demonstrates that use of quality-assured uterotonics would result in substantial reductions in the economic and health burden of PPH and contribute to decreasing maternal mortality and morbidity. Use of substandard uterotonics leads to increased out-of-pocket expenses and costs to health systems, which should be prevented to promote universal health coverage (UHC). Medicines quality assurance improves health outcomes and results in cost savings for governments to scale their implementation of UHC.